Quality customer service - Martin, William B. (Crisp Pub. Menlo ParkUS, 1993)
Presents four steps to quality customer service and four reasons for its importance. Explains how to identify and provide for customers' needs; how to handle complaints and difficult customers; and how to ensure that customers return.